Delayed type III hypersensitivity reaction with acute kidney injury in two dogs following administration of concentrated human albumin during treatment for hypoalbuminemia secondary to septic peritonitis. Issue 5 (11th July 2020) - Mazzaferro, Elisa M.; Balakrishnan, Anusha; Hackner, Susan G.; Forman, Marnin; Foster, JD; Calabro, Janine; Cianciolo, Rachel E.
Abstract: Objective: To describe 2 dogs with acute kidney injury secondary to type III hypersensitivity reaction to 25% human serum albumin (HSA). Case series summary: Two dogs were presented with evidence of septic peritonitis. The dogs were hospitalized following definitive surgical correction of a jejunal laceration following routine ovariohysterectomy, and removal of a jejunal foreign body. In the postoperative period, both dogs developed hypoalbuminemia and received 25% HSA. At the time of initial discharge, both dogs were doing well clinically and had normal renal parameters. Eleven and 18 days after HSA infusion, respectively, both dogs were re‐presented with clinical signs of inappetence, vomiting, and lameness that progressed to urticaria, peripheral and angioedema, and petechiae, consistent with a delayed type III hypersensitivity reaction. Treatment for the type III hypersensitivity reaction to HSA included administration of diphenhydramine and glucocorticoids. Despite partial resolution of edema and joint swelling, both dogs developed progressive azotemia together with hypoalbuminemia and proteinuria. One dog developed an anuric acute kidney injury (AKI). Both dogs were humanely euthanized. Histopathology of the kidneys of both dogs was consistent with immune complex deposition and vasculitis. New or unique information: Severe type III hypersensitivity reactions have been documented in healthy dogs and clinical patients following the administration of HSA. This report describes the first documented delayed type III hypersensitivity reaction in 2 dogs with septic peritonitis that resulted in AKI, glomerulonephritis, and oligo‐ to anuria in clinical patients following administration of 25% HSA.